2008
DOI: 10.1254/jphs.fp0071453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Antiepileptics on Behavioral and Electroencephalographic Seizures Induced by Maximal Electroshock in Mice

Abstract: Abstract. The changes of electroencephalogram induced by maximal electroshock were studied in comparison with behavioral seizures in mice. After electroshock, mice showed tonic flexor (TF) seizure, tonic extensor (TE) seizure, and clonic (CL) seizure, in this order of occurrence. At the same time, high frequency spike or spike and wave complex in the cortex was observed, and thereafter, the frequency of the spike or spike and wave complex gradually fell. The antiepileptics used in the present study, except for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Under pentobarbital anesthesia (60 mg/kg, i.p., Nembutal; Abbot Laboratories, North Chicago, IL, U.S.A.), the mice were fixed to a stereotaxic apparatus (SR‐5; Narishige, Tokyo, Japan). According to the atlas of Franklin and Paxinos (1996), monopolar screw electrodes were implanted in the right frontal cortex (FCOR, A: +3.0, L: +1.0), left occipital cortex (L‐OCOR, A: −4.3, L: −2.4), and right occipital cortex (R‐OCOR, A: −4.3, L: +2.4) (Murakami et al., 2008). A reference electrode was implanted in the occipital part of the cranium.…”
Section: Methodsmentioning
confidence: 99%
“…Under pentobarbital anesthesia (60 mg/kg, i.p., Nembutal; Abbot Laboratories, North Chicago, IL, U.S.A.), the mice were fixed to a stereotaxic apparatus (SR‐5; Narishige, Tokyo, Japan). According to the atlas of Franklin and Paxinos (1996), monopolar screw electrodes were implanted in the right frontal cortex (FCOR, A: +3.0, L: +1.0), left occipital cortex (L‐OCOR, A: −4.3, L: −2.4), and right occipital cortex (R‐OCOR, A: −4.3, L: +2.4) (Murakami et al., 2008). A reference electrode was implanted in the occipital part of the cranium.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, PTZ-induced seizure shows fast trains of spike discharges and subsequently a slow wave appears on the EEG (14,15). We have reported that EEG changes induced by maximal electroshock were a useful index to assess the potential of antiepileptic activity (16); however, there is little information about the detailed EEG changes induced by PTZ administration in animals, except for a few papers. It is presumed that the measurement of EEG changes will provide new information that cannot be obtained with only behavior observation; therefore, we measured EEG changes as well as seizure symptoms induced by PTZ in detail.…”
Section: Introductionmentioning
confidence: 99%